Analisis Religiusitas Individu Terhadap Pencegahan Dan Pendeteksian Cash Larceny - Nanda Iga Febrianti; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
This study seeks to analyze individual religiosity in reducing fraudulent behavior, especially cash larceny. The method used is interviews with informants. This research shows that individual religiosity can prevent fraud. However, this doesn't always work. Individual religiosity can change when under pressure, so they often forget the norms and religious values ​​themselves. In addition, the culture or habits of the company depend on the leadership, anti-fraud activities are still little implemented in the company..